2022
DOI: 10.23969/jrak.v14i2.5576
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a Career as a Public Accountant: Does Calling Matter?

Abstract: Public accountants are in great demand in Indonesia. However, the development of the new public accountant did not go as planned. This study aims to determine the antecedents that influence accounting students' intention to pursue careers as public accountants. This study's Social Cognitive Career Theory (SCCT) framework is extended by adding a Role Model and Calling. The participants in this study are 204 accounting students who have taken the auditing course. The findings of this study reveal that calling ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The test results indicate that self-efficacy plays a role in influencing the aspiration to become a Government Auditor. The outcomes of this study align with previous research conducted by Schoenfeld et al (2017), Umar & Bello (2019), Dewi & Lestari (2020), Hutami et al (2022), andNada &Afriyenti (2023). According to the SCCT theory, highly self-assured individuals are more inclined to aspire to challenging careers and have a determined intention to succeed (Lent et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The test results indicate that self-efficacy plays a role in influencing the aspiration to become a Government Auditor. The outcomes of this study align with previous research conducted by Schoenfeld et al (2017), Umar & Bello (2019), Dewi & Lestari (2020), Hutami et al (2022), andNada &Afriyenti (2023). According to the SCCT theory, highly self-assured individuals are more inclined to aspire to challenging careers and have a determined intention to succeed (Lent et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
“…Research conducted by Hutami et al, (2022) using the Theory of Planned Behavior (TPB) indicated that self-efficacy positively affects accounting students' intention to pursue a career as a sharia accountant. This finding aligns with the conclusions drawn from studies conducted by Schoenfeld et al (2017); Umar & Bello (2019); and Rahmawati et al, (2022), which found a positive correlation between self-efficacy and an individual's intention to pursue a career.…”
Section: Self-efficacy and The Goal Of Becoming A Government Auditormentioning
confidence: 99%
See 1 more Smart Citation
“…Further evaluation involved comparing the root Average Variance Extracted (AVE) values with inter-construct correlations. Each variable with AVE > 0.5 indicates successful construct validity testing (Hutami, Kholid, and Salsabilla, 2022). As depicted in Table 2, all AVE values exceed 0.50, meeting the specified minimum requirement.…”
Section: Discussionmentioning
confidence: 88%
“…This very low number of public accountants is certainly triggered by various factors (Fachrunnisa et al, 2022;Hutami et al, 2022). One of these triggers could be the lack of interest among students in working as public accountants after graduating from bachelor's degrees (Nabela et al, 2023) .…”
Section: Introductionmentioning
confidence: 99%